TRANSFORMASI KEBIJAKAN BERKELANJUTAN: INTEGRASI GREEN POLICY DALAM ADMINISTRASI NEGARA - Abdul Halil Hi. Ibrahim; Muhlis Hafel; Syaiful Madjid, Abdurrahman Kader (Adiba Aisha Amira, 2025)
The transformation of sustainable policies through the integration of the Green Policy in state administration marks a critical step in responding to increasingly complex environmental challenges. This green policy seeks to systematically adopt sustainability principles in the process of policy making and government practice. The impacts include reducing the ecological footprint, promoting innovation in green technology, reducing dependence on non-renewable resources, and reducing carbon emissions. In addition, this approach also creates new economic opportunities and increases global competitiveness. The success of this transformation depends heavily on the synergy between the government, society, and the private sector. These efforts are expected to support the achievement of sustainable development goals and realise a better future for the environment and future generations.